(untitled) (TEL Tempo, Espaço e Linguagem, 2025)
This article addresses grief in the digital age, where "digital immortality" redefines finitude, causing emotional overload and prolonged suffering. The spectacularization of online grief transforms pain into consumable content, affecting the intimacy of loss. The post-mortem right to be forgotten is discussed as a crucial ethical issue, given the gap in protocols and legislation for digital legacies. It urges the development of humanized policies that reconcile memory, privacy, and dignity, promoting healthy grieving in the 21st century.